Serological Investigation of Pneumonia as It Presents to the Physician's Office. (1993) - Langille, DB; Yates, L; Marrie, TJ
Abstract : Purpose: To define the etiology of pneumonia, using a battery of serological tests, among patients presenting to physicians' offices in Cumberland County, Nova Scotia from July 2, 1989 to July 1, 1990. Methods: Patients presenting to their physician's office with symptoms suggestive of pneumonia were invited to participate in the study by completing a questionnaire, having a chest radiograph and providing acute and convalescent phase serum samples. These serum samples were tested for antibodies to Mycoplasma pneumoniae, Coxiella burnetii, Legionella pneumophila, adenovirus, and influenza viruses A and B. Some of the samples were tested for antibodies to Chlamydia pneumoniae . Results: Seventy-five of the inception cohort of 203 patients had a chest radiograph compatible with pneumonia, a completed questionnaire and acute and convalescent phase serum samples. There were 39 females and 36 males with a mean age of 41.7 years. Twenty-six (35%) were admitted to hospital. The mortality rate was 3%. Forty-five per cent had a diagnosis made by serology: M pneumoniae, 22 (29%); influenza A virus, five (7%); C burnetii, L pneumophila, adenovirus, two (3%) each. Conclusions: While it is not possible to generalize about these findings because of ascertainment bias, the data suggest that M pneumoniae is a common cause of pneumonia presenting to a physician's office and that mortality is low in this group of patients.